Mobile Money As Drivers Of Women Msme Performance: The Moderating Effect Of Dynamic Capabilities - Mirza Hapsari Hasidin; Astil Harli Roslan; Ichsanuddin Akbar (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
This study aims to analyze the influence of mobile money on the performance of women's MSMEs, as well as test dynamic capabilities as a moderation variable that strengthens relationships in the model. The research uses a quantitative approach with a survey method. Data was collected through an online questionnaire distributed to 200 female MSME actors where respondents played the role of business owners or managers. The selection of respondents was carried out purposively with the criteria of women who actively run MSMEs and have experience using mobile money and/or accessing formal financial services in business activities. All indicators were measured using a five-point Likert scale from strongly disagree to strongly agree, with items adapted from previous literature and adjusted to the characteristics of local MSMEs. Data analysis was carried out using SEM PLS because it was able to test the relationship between constructs simultaneously while accommodating moderation testing. The test results show that the variables in the model have a meaningful influence on the performance of women MSMEs, with mobile money as the strongest driver through ease of transactions, payment efficiency, and acceleration of cash flow. Dynamic capabilities also contribute to improved performance because adaptive and innovative business actors are better able to optimize the benefits of digital financial services. In addition, the moderation effect emphasizes the existence of synergy, where the use of mobile money becomes more effective when MSMEs have higher dynamic capabilities. These findings emphasize the importance of expanding the adoption of digital financial services accompanied by strengthening the adaptive capabilities of women's MSMEs.